Following artifacts - Verena Halsmayer (Duke University, Center for the History of Political Economy (CHOPE), 2018)
The essay discusses the historiographical strategy of "following artifacts" in the history of contemporary economics. Following models as artifacts means (1) to follow the shifts and changes in their form and meaning; (2) to follow the ideas, theories, fictions, and imaginary worlds they provoke; and (3) to investigate the ways in which some of them stabilize and remain as infrastructures of economic reasoning in academic and policy realms, as well as the ways in which some of them either do not circulate at all or simply get lost. Such perspectives regarding the complexity and dynamics of knowledge creation lead out of the narrower history of disciplinary knowledge and, moreover, direct attention to different temporal scales.
Keywords: B2; B4; 330; artifacts; historiography; models; economic knowledge